"If people are wearing pink stuff they're probably not real fans": Exploring women's perceptions of sport fan clothing. Issue 5 (November 2019) - Sveinson, Katherine; Hoeber, Larena; Toffoletti, Kim
Highlights: We conceptualized clothing as artifacts. We theorized women consumers' decision making using third-wave feminism. Women sport consumers use team apparel to negotiate multiple aspects of their identity. Women are aware of consumer culture in marketing both gender and sport fandom. Women seek gender-neutral clothing to legitimize fan identities. Abstract: Given the growth in the female sport fan base of North American major league sports and the development and expansion of women's team-related apparel, the purpose of this study was to examine women sport fans' perceptions of team apparel. The authors collected data through in-depth interviews with 16 Canadian women who self-identified as fans of professional sport teams. They perceived a lack of options in team apparel, despite the development of women's clothing lines. Analysis of the aesthetics, symbolism, and instrumentality of team apparel using a third-wave feminist approach provides socio-cultural explanations for women fans' dissatisfaction with existing offerings. This approach advances understandings of the social circumstances shaping women's sport experiences as fans and the impact of gender on consumer engagement. Results suggest that sport teams need to recognize the diversity of women's gender identities and expressions and provide a wider range of clothing that demonstrate their status as authentic fans.